Prevalence Of Fungal Diseases In Medicinal Plants In Northern Region Of Bangladesh - Rahman, MA; Moni, ZR; Hussen, MA; Ansari, TH (SAARC Journal of Agriculture, 2020)
A season wise survey was conducted on the fungal diseases of some important cultivated medicinal plants in two consecutive years 2014 and 2015 in the northern region of Bangladesh. Eleven fungal diseases namely root rot (Fusarium solani) and leaf blight (Alternaria alternata) of Ashwagandha, leaf spot (Curvularia lunata) and collar rot (Fusarium oxysporium) of Alovera, powdery mildew (Erysiphe sp.) and root rot (Fusarium oxysporium) of Tulsi, collar rot (Fusarium oxysporium) and leaf spot (Collettotrichum gloeosporioides) of Kalmegh, tuberous rot (Fusarium solani) and stem rot (Fusarium oxysporium) of Satamuli, and root rot (Fusarium solani) of Basak were recorded. Most of the diseases were found in the rainy season’s comparative to other seasons. Among all the above-mentioned diseases, the powdery mildew (Erysiphe sp.) of Tulsi was found mainly in winter season. With the spreading of these fungal diseases on medicinal plants could be a set back to the industry associated with the formulation of its medicinal products. Therefore, this work may encourage other researchers to study these diseases further for development of proper management. SAARC J. Agri., 17(2): 197-212 (2019)